ANALYSIS STRUCTURE OF THE BOARDING HOUSE TEGAL PARANG AT SOUTH JAKARTA - Irpansyah, Kholly; Rohman, Fathur (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
Jakarta City is a city that became the heart of the unitary State of the Republic of indonesia has potential as the city develops. Jakarta is already good enough if compared to its neighboring cities ? city, seen from there is a lot of building skyscrapers. Therefore the population in this city is very solid plus the number of communities outside the city looking for work, education and so on, and many choose to find a place the residence then the role of the existence of an agency that handles problems a place to live and help with much needed to help the business community in order to be better, as there are Houses kost. Currently, the central building were built as high as five floors with one basement, exactly on JL. TegalParang Utara, South Jakarta.To meet the criteria of safety and service required the existence of a design careful planning. Therefore the imposition of planning process must comply with the SNI 1727-2013 as well as planning the structure of the building should be referred to with the SNI-2847-2013 reinforced concrete, which is the latest peratuaran which refers to the AISC and has adapted to the the latest materials technology development. In the calculation of earthquake engineering, this refers to the SNI 1726 ? 2012.?Based on data obtained from a Home Building project, tegalparangkost has an area of approximately 3224.86 m2. The author will meredesain a building material by using the concrete structure which consists of 5 (four) along with the basement 1 floor.?Analysis of the structure of the used software SAP2000, a material used for reinforced concrete beams, columns, roof and floor plates are plates. The results obtained in the form of analysis and design drawings of the structure of the building House kosttegalparang.??Key Words: Analysis, Boarding House TegalParang, Material, Reinforced Concrete, Columns, Beams, Plate.